Effects of Seed Mıxture Ratıo and Harvest Tıme on Forage Yıeld and Sılage Qualıty of Intercropped Berseem Clover Wıth Trıtıcale - Yücel, Celal; Avcı, Mustafa; Yücel, Hatice; Sevilmiş, Uğur; Hatipoğlu, Rüştü (FRESENIUS ENVIRONMENTAL BULLETIN, 2018)
Experiment was conducted during winter seasons of 2011-12 and 2012-13 years in order to determine the effects of seed mixture ratio and harvest time of intercropped berseem clover (Trifolium alexandrinum) with triticale (Triticosecale) on dry matter yield and silage quality under East Mediterranean (Cukurova) conditions. Berseem clover (BC) cv. Derya and triticale (T) cv. Tacettinbey were used as plant materials. The seed mixture ratios were sole crops BC and T, BC (80%) + T (20%), BC (60%) + T (% 40), BC (40%) + T (%60) and BC (20%) + T (80%). Forage harvest stages were beginning of flowering (HI), 50% flowering (H2) and full flowering (H3) stages of berseem clover. The experiment was established in a split plot design with four replications under lowland conditions. The mixture-ratios and harvest-stages were allocated as main plots and sub-plots, respectively. In addition to dry matter yield (DMY) and botanical composition, silage samples were evaluated for crude protein (CP), pH, acid detergent fiber (ADF), neutral detergent fiber (NDF) concentrations and digestible dry matter (DDM), relative feed value (RFV) and dry matter intake (DMI). The results of the study showed that the seed mixture of 60 % berseem clover + 40 % triticale and harvest at the 100% flowering stage of berseem clover were superior in terms of yield and selected quality parameters.
Keywords: Berseem clover; Triticale; Forage yield; Silage quality; Mixture ratio; Harvest stage